STUDY OF SOME COMPOUNDS ON PLANTS AS CANDIDATE OF HEPATITIS C ANTIVIRAL BY IN SILICO AND IN VITRO METHODS - Hermadi Saputro, Anjar
Hepatitis C is an inflammatory liver disease caused by the hepatitis C virus. Until now, there is no vaccine that can specifically prevent and treat hepatitis C infection. On the other hand, the discovery of new drugs from various sources including plants continues to be developed intensively. Therefore, the aim of this research was to study the interactions of 50 compounds on the hepatitis C virus and predicted their toxicity using in silico method, then the selected compounds were continued with in vitro anti-hepatitis C test and acute toxicity test on zebrafish embryos. First of all, molecular docking was carried out between the ligand or compound into the protein target using Autodock Tools® then visualized using BIOVIA Discovery Studio® . The binding free energy of the ligand or compound complex with the protein and amino acid residues in the complex then visualized and evaluated. The results of the molecular docking of each compound were continued into molecular dynamics simulation using Gromacs® for 200 ns then several parameters in the molecular dynamics simulation were analyzed such as RMSD, RMSF, RDF, SASA, Radius of Gyration, hydrogen bonds and binding free energy using MMPBSA and MMGBSA calculations. Toxicity predictions by in silico methods were done using Toxtree® and Vega® softwares, while predictions of compound pharmacokinetic profiles such as absorption, distribution, metabolism, excretion and toxicity (ADMET) were done using pkCSM® . Based on molecular docking the selected target proteins were 3FQL and 5E4F proteins because all compounds produced the lowest free binding energy on 3FQL or 5E4F proteins. The beta-sitosterol has the lowest energy with a value of -10.87 kkal/mol in the 3FQL protein and the hesperidin has the lowest energy with a value of -10.88 kkal/mol in the 5E4F protein. In the visualization of amino acid residues, the compound that produced the highest % similarity of amino vi acid residues with the amino acid residues of the native ligand-3FQL protein complex were the alpha-mangostin and nobiletin with a % similarity value of amino acid residues of 78.57%. Meanwhile, the compound that produced the highest % similarity of amino acid residues with the residues of the native ligand-5E4F protein complex was quercitrin with a % similarity value of amino acid residues of 60%. The results of molecular dynamics simulation showed that the compound that produced the lowest free bond energy value in the 3FQL protein was the mitragynin with binding free energy values of -47.63 kkal/mol in the MMPBSA calculation and -64.43 kkal/mol in the MMGBSA calculation. Meanwhile, the compound that produced the lowest binding free energy values for the 5E4F protein was the hesperidin with binding free energy values of -32.93 kkal/mol in the MMPBSA calculation and -45.36 kkal/mol in the MMGBSA calculation. The average of RMSD value was < 2.50 Å for both 3FQL and 5E4F proteins. The average of RMSF value was < 1.50 Å. The average of SASA value on the 3FQL protein was in the range of 238.09 – 245.92 nm2 and the average of SASA value on the 5E4F protein was in the range 189.17 – 196.17 nm2 . In the RDF analysis, the average of RDF value for the 3FQL protein was in the range of 4.24 – 4.55 g(r) and the average of RDF value for the 5E4F protein was in the range of 2.11 – 4.55 g(r). The average value of radius of gyration was in the range of 2.40 – 2.44 nm and the average value of radius of gyration produced for the 5E4F protein was in the range of 2.27 – 2.32 nm. Based on the results of in silico toxicity prediction analysis, several compounds were predicted to be safe based on Toxtree® software, they were ferulic acid, rosmarinic acid, syringic acid, bakuciol, capsaicin, cinnamaldehyde, citronellol, and trans-anetol. Meanwhile, based on toxicity predictions using Vega® tox software, the results showed that the ferulic acid, chlorogenic acid, rosmarinic acid, syringic acid, citronellol and eugenol were predicted to have lower toxicity than other compounds. In toxicity prediction using Vega® ecotox software, the cinnamaldehyde, eucalyptol and alliin were predicted to have lower toxicity than other compounds in algae, Daphnia magna and fish. Based on the results of ADMET analysis using pkCSM®, the prediction of absorption parameters showed that all compounds were predicted to have good absorption in the human intestine because they had an absorption value of >30%. In terms of distribution parameter, several compounds such as beta-sitosterol, cinnamaldehyde, citronellol, eucalyptol, caryophyllene oxide, mitragynine, trans-anethole, stigmasterol, thymoquinone, bakuchiol, and eugenol were predicted to penetrate the blood-brain barrier. In metabolism prediction, the mitragynine compound was predicted to be an inhibitor of CYP2D6. In the excretion prediction, it was predicted that all compounds could be excreted by the human body. Then in predicting toxicity, several compounds that were predicted to be toxic to the liver vii were mitragynine, capsaicin, piperine, umbeliferon and anti-hepatitis C drugs such as dasabuvir, sofosbuvir and simeprevir. Based on the results of the in vitro anti-hepatitis C test on Huh7 cells, it was found that the alpha-mangostin and piperine showed anti-hepatitis C activities with IC50 of 2.70 ± 0.92 µM and 52.18 ± 3.20 µM respectively. Then, based on the results of acute toxicity testing on zebrafish embryos, the LC50 or LD50 results for alpha-mangostin, beta-sitosterol, piperine, hesperidin, nicotiflorin and quercitrin were 28.02; 316.04; 19.29; 162.42; 154.43; 165.10 ppm respectively. Cytotoxicity test results on Huh7 cells showed that alpha-mangostin compounds in the concentration range 6.25 - 25 µM, piperine compounds in the concentration range 15.62 - 125 µM and sofosbuvir compounds in the concentration range 0.015 - 1 µM produced % cell viability above 80%. Based on the relationship between the results of in silico and in vitro studies, it can be concluded that the alpha-mangostin compound had the most potential to be developed as an anti-hepatitis C.